On Computing Mental States - Ranatunga, L. P. (Malaysian Journal of Computer Science, 1996)
An expert system has been created based on the Theravada Buddhist theory of the mind to compute coexisting mental states of ordinary human beings. Given one state of the mind, the system finds other coexisting set of states. The expert system supplies information about the constituents of consciousness. A stochastic model of impulsive thought moments in Buddhist psychology has been constructed.